Pulse Granulomas of the Gastrointestinal Tract and Gallbladder: Report of Five Cases. (13th July 2017) - DeRoche, Tom C.; Gates, Gregory A.; Huber, Aaron R.
Abstract : Hyaline rings with admixed multinucleated giant cells characterize pulse granulomas; the term pulse refers to edible seeds of legume vegetables. The etiology has been controversial, with theories including vascular degenerative changes or a reaction to vegetable material; ultrastructural studies and experimentally induced lesions in animals favor the latter. This lesion is typically seen in the oral cavity, with only rare reports in the gastrointestinal tract and gallbladder. We herein describe five cases of pulse granulomas identified in these sites. All cases contained foreign-body giant cells and vegetable debris within or near hyaline rings. Pulse granulomas may form mass lesions but are usually an incidental finding on microscopic examination. In incidentally detected cases, recognition of pulse granulomas can suggest a mural abscess, fistula, or perforation of the gut, findings which may not be grossly apparent. The presence of vegetable material in all five cases further supports an exogenous pathogenesis.